PENGARUH EFEKTIVITAS PROGRAM KELUARGA BERENCANA TERHADAP PENGENDALIAN PERTUMBUHAN PENDUDUK DI WILAYAH KERJA PT.MNHE PALANGKARAYA - angreani, yuni; Maolinda, Winda; Hidayah, Nur (LPPM Universitas Sari Mulia, 2024)
Background: High population growth can become aserious enough problem if it is not immediately resolved, the high and uncontrolled population growth rate will affect the decreasing level of community and family welfare.Objective: Analyzing the influence of the effectiviness of the family planning program on controlling population growth at the PT MNHE Palangkaraya. Method: This study took 9 people consisting of 1 doctor, 3 midwife, 1 midwife assistant, and 4 KB acceptors. Collecting data using interview tecniques, analysis of research data is descriptive. Result: The majority of respondents have received sufficient information about family planning programs and are aware of the importance of family planning programs in controlling population growth.Conclusion: Socialization of the family plannung program has started to show results, but there are still some obstacles such as people who dont want to have family planning, the family planning program had been quite effective in reducing the rate of population growth in the working area of PT.MNHE Palangkaraya. Keywords: Family Program, Effectivieness, Popolation Growth, Planning